VALUE OF THE PROGNOSTIC MARKERS OF THE TUMOR PROGRESSION P53, P21WAF1/CIP1, P63 AND KI-67 IN THYROID TUMORS - MuzhichukА.V.; Afanasyeva, N.I.; Muzhichuk, V.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
196 samples of removed thyroid gland tissue were studied. The expression of p53, p21WAF1/CIP1, p63, and proliferation marker Ki-67 were studied in the sections. The greatest increase in expression level of p53, p63, Ki-67 and p21WAF1/CIP1 in comparison with paraneoplastic, benign and normal thyroid tissue in tumor tissue of differentiated thyroid cancer was observed. Changes in the expression of p21WAF1/CIP1, p63 and Ki-67 compared with unchanged thyroid tissue in the benign tumors and in paraneoplastic tissue had general tendencies. These changes had the same orientation, as well as in cancer of the thyroid gland, where they were most pronounced. Determination of p21WAF1/CIP1 and p63 expression in benign thyroid parenchyma may be a marker of it malignant transformation, and patients will be at risk for cancer. Ki-67 is an objective indicator of proliferative activity of thyrocytes, which may be used as clarifying the biological characteristics of tumors.